HER-2/neu overexpression correlates with increased expression of VEGF in primary breast carcinoma - Nageswar Sahu; Anurag Sharma; Urmila Senapati (International Journal of Medical Research and Review, 2016)
Background: Overexpression of HER-2/neu is associated with up-regulation of vascular endothelial growth factor (VEGF) in human breast cancer cells in vitro. Preclinical experiments indicate that increased expression of VEGF may in part mediate the biologically aggressive phenotype of HER-2/neu overexpressing human breast cancer. It was the purpose of this study to: (a) evaluate the association between HER-2/neu and VEGF expression in a cohort of primary breast cancer patients; (b) find out any association of HER-2/neu or VEGF with traditional histologic prognostic parameters.Materials and Methods: HER-2/neu and VEGF were measured by immunohistochemistry in 70 cases of newly diagnosed primary breast cancers and the relation between these two markers and their relations with traditional prognostic factors were analyzed by statistical methods.Results: Our findings indicate a significant positive association between HER-2/neu and VEGF expression. VEGF did not show significant association with tumor size, histologic grade or lymph node status. HER-2/neu overexpression was maximum in grade II, followed by grade I and III with a significant p value (<0.001). But HER-2/neu didn’t have any association with tumor size or lymph node status.Conclusion: The positive association between HER-2/neu and VEGF expression implicates VEGF in the aggressive phenotype exhibited by HER-2/neu overexpression, and supports the use of combination therapies directed against both HER-2/neu and VEGF for treatment of breast cancers that overexpress HER-2/neu. The unusual association found between HER-2/neu and grade of tumor may be due to uneven distribution of cases among different grades of tumor.